Soft Robotics - Whitesides, George M. (Angewandte Chemie (International ed.), 2018)
This description of “soft robotics” is not intended to be a conventional review, in the sense of a comprehensive technical summary of a developing field. Rather, its objective is to describe soft robotics as a new field—one that offers opportunities to chemists and materials scientists who like to make “things” and to work with macroscopic objects that move and exert force. It will give one (personal) view of what soft actuators and robots are, and how this class of soft devices fits into the more highly developed field of conventional “hard” robotics. It will also suggest how and why soft robotics is more than simply a minor technical “tweak” on hard robotics and propose a unique role for chemistry, and materials science, in this field. Soft robotics is, at its core, intellectually and technologically different from hard robotics, both because it has different objectives and uses and because it relies on the properties of materials to assume many of the roles played by sensors, actuators, and controllers in hard robotics. Robotics is at an early stage of technological development, and it's when machines and humans begin to work together and/or to compete that things change and get really interesting. Soft robotics will be an essential part of that change. Chemistry and materials science should not miss the opportunity to be a part of it.